2017
DOI: 10.1021/acscatal.7b00104
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective C–H Annulation of Indoles with Diazo Compounds through a Chiral Rh(III) Catalyst

Abstract: The asymmetric C–H annulation of O-pivaloyl 1-indolehydroxamic acid with donor/acceptor diazo compounds has been achieved for the first time, to the best of our knowledge, by using a rhodium catalyst embedded in a chiral binaphthyl backbone. This protocol constitutes a straightforward route for the synthesis of a new family of 1,2-dihydro-3H-imidazo­[1,5-a]­indol-3-one derivatives having a quaternary carbon stereocenter in high yields and excellent enantioselectivity (up to 98:2 er).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…By using N ‐(pivaloyloxy)carbamoyl as oxidative directing group, 1 mol % [Cp*RhCl 2 ] 2 as catalyst and MeCN as solvent, a variety of 1H‐imidazo[1,5‐a]indol‐3(2H)‐one derivatives 70 could be obtained in good yields under mild conditions via a C−H activation/[4+1] cyclization. Since this C−H activation/cyclization constructed a quaternary carbon stereocenter in the product, in 2017, the Song group successfully developed an asymmetric protocol of this reaction (Scheme B) . They designed an asymmetric Rh complex 73 and found that this novel catalyst could efficiently promote an enantioselective C−H activation/[4+1] cyclization of indole‐ N ‐carboxamides 71 and diazo compounds 72 for the synthesis of the single enantiomer of 1H‐imidazo[1,5‐a]indol‐3(2H)‐one derivatives 74 .…”
Section: Indole‐n‐carboxamides In C−h Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…By using N ‐(pivaloyloxy)carbamoyl as oxidative directing group, 1 mol % [Cp*RhCl 2 ] 2 as catalyst and MeCN as solvent, a variety of 1H‐imidazo[1,5‐a]indol‐3(2H)‐one derivatives 70 could be obtained in good yields under mild conditions via a C−H activation/[4+1] cyclization. Since this C−H activation/cyclization constructed a quaternary carbon stereocenter in the product, in 2017, the Song group successfully developed an asymmetric protocol of this reaction (Scheme B) . They designed an asymmetric Rh complex 73 and found that this novel catalyst could efficiently promote an enantioselective C−H activation/[4+1] cyclization of indole‐ N ‐carboxamides 71 and diazo compounds 72 for the synthesis of the single enantiomer of 1H‐imidazo[1,5‐a]indol‐3(2H)‐one derivatives 74 .…”
Section: Indole‐n‐carboxamides In C−h Activationmentioning
confidence: 99%
“…Since this CÀ H activation/cyclization constructed a quaternary carbon stereocenter in the product, in 2017, the Song group successfully developed an asymmetric protocol of this reaction (Scheme 18B). [27] They designed an asymmetric Rh complex 73 and found that this novel catalyst could efficiently promote an enantioselective CÀ H activation/ rivatives 74. Typically, this asymmetric reaction should be conducted at À 30°C in acetone by the cooperative effect of 2.5 mol % Rh catalyst, 20 mol % AgSbF 6 and 1 equivalent of CsOAc.…”
Section: Reaction Of Indole-n-carboxamides With Diazo Compoundsmentioning
confidence: 99%
“…Catalyst structures of unique ligands for 32-35. [77][78][79][80] catalyst 32, which bears a diphosphazane monoxide-derived ligand, produces ethylene copolymers with high percentages of methyl acrylate (MA) and butyl vinyl ether incorporation (6.8 and 4.4 mol%, respectively) at temperatures as high as 80 ∘ C, albeit only reaching molecular weights (M n ) of 6.1 and 2.8 kg mol -1 . 77 In contrast, Pd phosphine phosphonic amide catalyst 33 was shown to be highly active for ethylene polymerizations up to 100 ∘ C (activity = 134 × 10 5 g (mol Pd) −1 h −1 ), and was able to produce ethylene/MA copolymers with incredible MA incorporation percentages of up to 33 mol% at 100 ∘ C. 78 Similarly, Pd-based phosphine sulfonate catalyst 34 and Ni-based phosphine sulfonate catalyst 35 were developed by Chen and co-workers and evaluated for their high-temperature performance (Fig.…”
Section: Other Ligand Structuresmentioning
confidence: 99%
“…[1][2][3] Due to the superior properties of tolerance towards polar functional groups and the development of some innovative catalyst design strategies, [4] α-diimine Ni(II) and Pd(II) catalysts can catalyze the copolymerization of ethylene with polar-functionalized co-monomers. [5,6] Moreover, the topologies of polymer chains (ranging from linear to hyperbranched structures) can be controlled by simply modifying the catalyst's ligand structure [7][8][9][10][11][12][13][14][15][16][17][18][19] and polymerization conditions such as temperature [20] and ethylene pressure. [21][22][23] Owing to the sterically bulky ortho substituents on the aryls of the ligand that are positioned in axial sites of the central metal, the chain transfer reaction is greatly suppressed, and high-molecular-weight hyperbranched polyethylene (with ca 100 branches per 1000 carbons) can be prepared using typical α-diimine Ni(II) catalysts (Figure 1, B-Cat).…”
Section: Introductionmentioning
confidence: 99%